Exemplary water resources management in semi-arid areas - Lhu, Samuel Kian Eng. (2008)
Singapore has been relying on Malaysia to supply part of its daily water consumption since 1965. Such a traditional alternative for municipal water supply may soon be less appropriate or even impractical as the water agreements with Malaysia are expiring in year 2011 and 2061, respectively. Water reuse may thus surface as a viable and attractive alternative for the provision of municipal water supply.